Influencia de modelos exitosos de intervención educativa sobre salud bucodental en la higiene oral. - David Staly, Hidalgo Riofrío (2021)
ABSTRACT Oral health is a determining factor in health and quality of life, depending on the health burden, its representation, and its relationship with the different diseases. The burden of oral health morbidity is heterogeneous throughout the world, with the highest-burden in low- and middle-income countries due to inappropriate interventions. That is why the research aimed at analyzing the influence of successful models of educational intervention on oral health on oral hygiene. The methodology used was documentary since a search was carried out in various search engines of academic prestige such as Google scholar, Dialnet, Research gate, PubMed, Medigraphic, Scielo, Science Direct, Springer, Elsevier, Redalyc, Hindawi, published in the period 2010 and 2020. Where 849 obtained articles, after applying inclusion and exclusion criteria, 80 articles, which were analyzed according to the number of citations (ACC) and the impact of the journal (SJR), leaving a total of 53 articles with which the investigation was carried out. With the development of the research, it was possible to conclude those successful models of oral health educational intervention influence oral hygiene. Because educational strategies by providing practical knowledge allow the development of skills for self-care and care of the immediate environment, thereby creating Favorable environments for the acquisition and promotion of healthy habits at the oral level. Keywords: educational intervention, intervention models, oral health, oral hygiene, health promotion. Reviewed by: Mgs. Marcela González Robalino English Professor c.c. 0603017708